Constitutive Model and Damage Evolution of Mudstone under the Action of Dry-Wet Cycles - Ming Hu; Yuanxue Liu; Linbo Song; Yu Zhang (Advances in Civil Engineering)
Mudstone is a natural type of geological material, which has different ways of mechanical response between natural state and dry-wet cycles. According to the complex damage theory of geological materials, rock masses can be considered as a composite material consisting of the structure phase and damage phase. The essence of the damage of rock masses is a damage evolution process, during which the deformation energy of the structure phase converts into dissipation energy of the damage phase, and the energy dissipation from phase transformation promotes the structure phase to change into the damage phase. In this study, a customized model test container and a novel test method are applied to study the decay rate of mudstone under different temperatures and over multiple dry-wet cycles. The decay rate and the damage variable are connected with each other and applied to the damage constitutive equation based on the energy principle to set up the damage evolution equation under the coupled action of dry-wet cycles and loads. Comparison of the proposed model with test results in a literature identifies the rationality of the established model and properly reflects the damage evolution of mudstone.